Utilization of Digital Marketing for Micro, Small and Medium Enterprises in Dandangan Village. - Kurniawan, Rony; S, Edy Djoko; Prasojo, Aji; Cindia, Ike; Nuansari, Shindy Dwita (Edumedia Solution, 2025)
Digital transformation presents a major opportunity for MSMEs to expand markets and improve efficiency. In Dandangan Village, Kediri, many MSMEs use social media and e-commerce platforms, yet market reach remains limited and digital marketing knowledge is lacking. A one-month community service program provided training and outreach to enhance MSMEs’ digital literacy, including the use of mind maps as marketing planning tools. Results showed improved digital promotion skills, including public speaking during live selling. The use of mind maps helped MSMEs analyze markets, schedule content, and monitor digital performance. This program demonstrates that targeted assistance can sustainably strengthen MSMEs’ digital capabilities.